The Legal Challenges of The Tenancy Contract in Dubai: A Critical Analysis - Sanna, Ahmed Ibrahem (South Asian Journal of Social Sciences and Humanities, 2023)
The expansion of Dubai's real estate industry engenders a major economic importance to the region however, challenges are also imminent. In support of the growth in the sector, various forms of legislations and laws were enacted to support the tenancy contract such as Law No. 26 of 2007 Regulating Relationship between Landlords and Tenants in the Emirate of Dubai and Law No. 33 of 2008 amending for Law No. 26 of 2007. By using doctrinal legal research methodology, this article aims to examine the legal challenges of the tenancy contract in Dubai. The primary and secondary data are collected through the library approach and then analysed using critical approach. It is discovered that the non-existence of the long-term laws on lease contract remains an issue in Dubai. This is evidently clear in situations where the lease agreement has ended, and the property owner intends to make alterations deemed beneficial to the property's value. In such cases, a conflict arises if the tenant refuses to vacate the property. It is suggested that article No. 25/2 in Law No. 33 of 2008 should be amended in order to allow the lessor to vacate the property and obtain the required approvals to make changes to the property. The law should lay emphasis on the great coordination between the entities authorised to obtain the necessary licenses to enforce the Article 25/2 in Law No. 33 of 2008 as well.
Keywords: Tenancy agreement; Legislation; real estate; Eviction; Contract